2013
DOI: 10.1002/nau.22355
|View full text |Cite
|
Sign up to set email alerts
|

Urethral sphincter function before and after radical prostatectomy: Systematic review of the prognostic value of various assessment techniques

Abstract: MRI and UPP might be valuable preoperative diagnostic tools in patients waiting for RRP. However, more and larger studies are needed to show the exact role of MRI and UPP in the preoperative management of patients waiting for RRP and for whom post-operative incontinence is a big concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…The ratio of the levator ani muscle to PV did not show an influence in our study, nor did the urethral volume, as previously reported by Von Bodman et al [11]. As Dubbelman et al [21] reported, the urethral sphincter could be measured as MUL by MRI: our definition of UWT matched with the width of the sphincter. We are unsure why UWT had an influence on UI; perhaps, this influence is due to a hypertrophy of the urethral striated muscle, but we found no reports of this in the literature and thus do not know the underlying mechanism.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The ratio of the levator ani muscle to PV did not show an influence in our study, nor did the urethral volume, as previously reported by Von Bodman et al [11]. As Dubbelman et al [21] reported, the urethral sphincter could be measured as MUL by MRI: our definition of UWT matched with the width of the sphincter. We are unsure why UWT had an influence on UI; perhaps, this influence is due to a hypertrophy of the urethral striated muscle, but we found no reports of this in the literature and thus do not know the underlying mechanism.…”
Section: Discussionsupporting
confidence: 83%
“…Our study is not novel and is based on others such as Myers et al [17] and Mikuma et al [4] who reported the anatomy of the pelvic floor by MRI in 1998 but focused on coronal sequences. Coakley et al [18] in 2002 reported that a longer membranous urethra is associated with a more rapid return to continence, as did Paparel [19], Hakimi [20] and Dubbelman [21]. But Song [10] and Von Bodman [11] found as predictive factor the ratio of levator ani muscle to the PV and urethra, respectively, to be predictive factors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is interesting that there were no differences in UPP at rest. There are controversial findings in the published literature with urethral closure pressures at rest being worse in men with PPI in several studies but no difference found in others . However, all of these studies evaluated urethral pressures at rest only.…”
Section: Discussionmentioning
confidence: 98%
“…The evidence for pelvic floor dysfunction or for the diagnosis and or assessment of DFV in men is even less than for women, although imaging before and especially after radical prostatectomy, in men with post prostatectomy incontinence is gaining attention …”
Section: Pathophysiology Of Urethral Dysfunction In Menmentioning
confidence: 99%